2013
DOI: 10.1029/2012jb009382
|View full text |Cite
|
Sign up to set email alerts
|

Source directionality of ambient seismic noise inferred from three‐component beamforming

Abstract: [1] The increased use of ambient seismic noise for seismic imaging requires better understanding of the ambient seismic noise wavefield and its source locations and mechanisms. Although the source regions and mechanisms of Rayleigh waves have been studied extensively, characterization of Love wave source processes are sparse or absent. We present here the first systematic comparison of ambient seismic noise source directions within the primary (~10-20 s period) and secondary (~5-10 s period) microseism bands f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 74 publications
3
45
0
Order By: Relevance
“…R g waves recorded on the Z component show a stronger azimuthal dependence compared to the L Q / L g energy recorded on the T component. Previously reported directional similarities between R g and L Q energy in the secondary microseism band [e.g., Nishida et al , ; Hadziioannou et al , ; Behr et al , ] are partially present in our results, but deviations occur, especially for directions where R g is weak. At the lowest frequency ( f 1 = 0.35 Hz), we observe the Z component energy to be almost twice the strength of the T component; however, it is likely that Z / T ratios are regionally dependent especially for seismometers sited in sedimentary basins [ Koper and Burlacu , ; Juretzek and Hadziioannou , ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…R g waves recorded on the Z component show a stronger azimuthal dependence compared to the L Q / L g energy recorded on the T component. Previously reported directional similarities between R g and L Q energy in the secondary microseism band [e.g., Nishida et al , ; Hadziioannou et al , ; Behr et al , ] are partially present in our results, but deviations occur, especially for directions where R g is weak. At the lowest frequency ( f 1 = 0.35 Hz), we observe the Z component energy to be almost twice the strength of the T component; however, it is likely that Z / T ratios are regionally dependent especially for seismometers sited in sedimentary basins [ Koper and Burlacu , ; Juretzek and Hadziioannou , ].…”
Section: Discussionsupporting
confidence: 83%
“…The generation of Love waves in the secondary microseism range is currently not fully understood. Previous research found Rayleigh and Love waves to originate from similar directions [e.g., Friedrich et al , ; Nishida et al , ; Hadziioannou et al , ; Behr et al , ], hence hinting at a similar source area. As potential candidates for their generation, coupling with the seafloor topography (e.g., seamount) or some type of scattering process have been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Figure shows the nine cross‐correlograms obtained for a representative station pair (Dar2 and Dar3). Only the TT component exhibits high energy propagating in both directions, suggesting a more diffuse source of noise than for the other components; this inference is consistent with other observations in NZ [ Behr et al ., ]. The other components exhibit distinctive differences in amplitude for positive and negative lags, and thus for waves propagating in opposite directions.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the literature on the SM noise sources focuses on the Pacific and Atlantic oceans (e.g. Haubrich & McCamy 1969;Friedrich et al 1998;Chevrot et al 2007;Gerstoft & Tanimoto 2007;Brooks et al 2009;Koper et al 2010;Behr et al 2013) or on the global scale (Aster et al 2008;Gerstoft et al 2008;Stutzmann et al 2012) and very few on the Indian (e.g. Koper & De Foy 2008;Sheen 2014) and the Southern oceans (e.g.…”
Section: Introductionmentioning
confidence: 99%